GIANT HAEMANGIOMA OF NASOPHARYNX: A RARE CASE OUTCOME - Iftikhar, Haissan; Siddiqui, Moghira Iqbaluddin (Journal of Ayub Medical College Abbottabad, 2017)
A 60 year old female presented to us with a 5 year history of progressive right sided nasal obstruction and recurrent epistaxis. On examination lesion was seen in the right nostril which was firm and bled on probing. CT-scan paranasal sinuses showed a right sided lesion of nose and nasopharnyx obstructing posterior nasal choanae. Dimensions were reported to be 9 x 4.1 x 3.8cm. A punch biopsy was taken in operating room under general anesthesia which resulted in profuse bleeding. Suction cautery was used to control bleeding and the nose was packed. The mass was firm to hard and provided resistance during the time of biopsy. On second post-operative day the mass visibly changed its color and became blackish in appearance. Patient had an episode of cough in the evening and expelled out the entire mass orally. A 60-year-old female presented to us with a 5-year history of progressive right sided nasal obstruction and recurrent epistaxis. On examination lesion was seen in the right nostril which was firm and bled on probing. CT-scan paranasal sinuses showed a right sided lesion of nose and naso-pharnyx obstructing posterior nasal choanae. Dimensions were reported to be 9Ã—4.1Ã—3.8 cm. A punch biopsy was taken in operating room under general anaesthesia which resulted in profuse bleeding. Suction cautery was used to control bleeding and the nose was packed. The mass was firm to hard and provided resistance during the time of biopsy. On second post-operative day, the mass visibly changed its colour and became blackish in appearance. Patient had an episode of cough in the evening and expelled out the entire mass orally. Keywords: Hemangioma; Head and neck; Otolaryngology